Savant: A Framework for Supporting Content Accountability in Information Centric Networks - Diarmuid Ó Coileáin; Donal O'Mahony (EAI Endorsed Transactions on Cloud Systems, 2016)
The Information Centric Networking (ICN) paradigm offers solutions to some of the functional and performance limitations of the current Internet architecture by offering secure, efficient and scalable mechanisms for the delivery of content to end-users. However, ICN architectures fail to provide adequate content accountability for the content distribution process. (We use accountability and feedback interchangeably to refer to the logging information collected as part of the content distribution process). In this paper we propose the Savant architecture, which is a scalable accountability framework for ICN content distribution. We outline our current work and some preliminary results, which demonstrate the viability and scalability of the Savant architecture. Finally, we briefly outline avenues for future work.